ISLAM AND MODERN WORLD: MAIN DIRECTIONS OF RESEARCH - Кудін, О. О. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article represents the approaches to the Islam religion, its features and functioning in the modern processes of world globalization.